2018
DOI: 10.1002/adtp.201800069
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐Targeting IR‐780 Dye and Its Derivatives: Synthesis, Mechanisms of Action, and Theranostic Applications

Abstract: Mitochondria are important targets in diverse physiological and pathological conditions associated with cell survival and death. The characterization of mitochondria‐targeting agents is highly useful to the understanding of mitochondrial functions and the development of targeted therapeutic strategies. IR‐780, a prototypical near‐infrared (NIR) heptamethine cyanine dye, has been recently identified as the first mitochondria‐targeting multifunctional NIR dye, it has excellent optical imaging and therapeutic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 86 publications
1
33
0
Order By: Relevance
“…The mitochondrion, which is structurally characterised by a double membrane separated by the intermembrane space, exhibits a highly negative transmembrane potential as a result of the process of mitochondrial respiration whereby the proton pumps in the inner mitochondrial membrane transport protons onto the intermembrane space . This large potential distinguishes it from other subcellular organelles and has inspired the successful development of optically active probes that exploit it selectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrion, which is structurally characterised by a double membrane separated by the intermembrane space, exhibits a highly negative transmembrane potential as a result of the process of mitochondrial respiration whereby the proton pumps in the inner mitochondrial membrane transport protons onto the intermembrane space . This large potential distinguishes it from other subcellular organelles and has inspired the successful development of optically active probes that exploit it selectively.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a range of diagnostic imaging techniques, such as radioisotope labelling, magnetic resonance imaging and positron emission tomography, are employed for monitoring subcellular organelles . Recently, approaches exploiting fluorescence emission have been developed for the investigation of specific organelles such as mitochondria, representing a powerful class of imaging strategies, on account of their ability to translate molecular recognition into highly discriminative and easily detected optical signals …”
Section: Introductionmentioning
confidence: 99%
“…This result indicated that after entering tumor cells, PIH-NO could escape from lysosomes, which is similar as previous study. More importantly, IR780 can preferentially accumulate and be retained in mitochondria 47 . Next, 4T1 cells were stained with MitoTracker Green to verify whether PIH-NO could target the mitochondria of cancer cells after incubation with PIH-NO.…”
Section: Resultsmentioning
confidence: 99%
“…1g ). Lipophilic cationic property of NIR fluorescent dye is necessary for targeting mitochondria, which explains mitochondria-preferential accumulation of IR-61 32 34 . Concurrently, we confirmed that IR-61 was distributed particularly in the mitochondria of ATMs (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%